Prevalence of relevant early complications during the first 24 h on a normal ward in patients following PACU care after medium and major surgery: a monocentric retrospective observational study - Würth, Anouk; Hackert, Thilo; Böckler, Dittmar; Feißt, Manuel; Haag, Sabine; Weigand, Markus A.; Brenner, Thorsten; Schmoch, Thomas (Langenbeck's archives of surgery, 2024)
Even today, it remains a challenge for healthcare professionals to decide whether a clinically stable patient who is recovering from uncomplicated medium or major surgery would benefit from a postoperative intensive care unit (ICU) admission, or whether they would be at least as adequately cared for by a few hours of monitoring in the post-operative care unit (PACU).
Online veröffentlicht: 30. September 2024
Gesehen am 19.03.2025